Interpretation of Anthropomorphism Verses by the "Salaf" Generation in Tafsir Al-Tabari: Interpretasi Ayat Anthropomorphism oleh Generasi "Salaf" dalam Tafsir Al-Tabari - Romadlon, Dzulfikar Akbar; Astutik, Anita Puji; Hikmah, Khizanatul (Procedia of Social Sciences and Humanities, 2022)
This article will explain the interpretation of anthropomorphism verses by the Salaf generation, as recorded in Tafsir At-Tabari. This study is important because the verses of anthropomorphism are still being debated now. Sometimes, it creates divisions among Muslims, and each group states that they are the most following the "Salaf" generation or the generation that lived in the first three centuries hijriyyah. This study uses a literature study with the primary source being "Tafsir At-Tabari," written around 270 to 290 H by Imam Abu Jarir At-Tabari (310 H), which narrates the scholars' interpretation of the Salaf generation. This study indicates that the salaf scholars have two attitudes in interpreting the Anthropomorphism Verse. Some scholars interpret the anthropomorphism verse by understanding it as it is. Others argue that the verse is a figure of speech, so they do ta'wil or a method of interpretation by shifting the outward meaning of the text into another meaning that fits the context of the verse.